PENGARUH PENDEKATAN TaRL TERHADAP HASIL BELAJAR IPAS KELAS VI B SDN PEDURUNGAN KIDUL 01 - Kuswanto, Sinta Indriyani; Untari, Mei Fita Asri; Pramono, Ipnu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Students have various characteristics, including learning abilities. These differences result in them having different methods of receiving, interpreting and conveying information. Teachers can adjust teaching and assessment by paying attention to students' needs and abilities, one of which is by implementing the TaRL approach in the learning process. The purpose of this research is to determine the effect of implementing the TaRL approach on student learning outcomes in science learning. This research is a mixed method research. This research combines two methods, namely quantitative methods and qualitative methods to strengthen the results of the research. The subjects of this research were students in class VI B at SD Negeri Pedurungan Kidul 01 with a total of 23 students. The research instruments used to measure learning outcomes are pretest and posttest scores. The research design applied was one group pretest-posttest design. The data obtained was then tested using the normality test, paired sample t-test hypothesis test, and the N-Gain test. The research results showed that the average learning score of students before being treated with the TaRL approach was 45.56, while after being given treatment, this score increased to 85.47. The t test analysis with a significance level shows a value of 0.000, which is smaller than 0.05, indicating a significant influence. Apart from that, the N-Gain test result of 0.7421 is in the high category, which shows the effectiveness of implementing the TaRL approach. Based on the results of this research, it can be concluded that the application of the TaRL approach has a significant and effective influence on student learning outcomes, especially for students with a low initial level of ability.